NECESIDAD DE ELIMINAR LA CONTRIBUCIÓN ECONÓMICA QUE BRINDA EL ESTADO PARA CON LOS PARTIDOS POLÍTICOS, E IMPLEMENTAR NUEVAS FORMAS DE HACER CAMPAÑA POLÍTICA EN NUESTRO PAÍS - Encarnación Hidalgo, Ángel Manrique (2016)
This thesis takes as its theme I wrote the following, "NEED TO ELIMINATE THE ECONOMIC BENEFITS PROVIDED BY THE STATE WITH POLITICAL PARTIES, AND IMPLEMENT NEW WAYS TO MAKE POLITICAL CAMPAIGN IN OUR COUNTRY", which is largely based on the parties politicians existing in our country, its history, the role they play in our society, what their pros and cons are, the importance of its existence, the political power they represent, and something very important, and that is precisely what I I've been doing this research, which is the subsidy that they receive to stay formed as such, the economic damage they bring to the Ecuadorian people, and because it should eliminate such financial contributions the state provides for these. To begin with developing this thesis, we must know the concept of political party, to understand the role within a State, they are politically organized mass moving in our country, those who incite society to form one group of people who share certain ideology, thought, customs and economic, political and social interests within a state. Political parties have developed according to their needs and competition resulting with their counterparts, they have developed strategies and have won important victories that have led them to take control of the country and stay in power, but we do not know is that in order to succeed as games much money is spent, which 8 albeit are private contributions , typical of his followers and sympathizers related but are not the only figures used in political campaigns that they perform, a lot of this comes from the state, the Ecuadorian people, millions of dollars which the state subsidizes for with these organizations, money that could well be used in social work, or any other system that benefits society, but not to these groups called parties. For these and other reasons it is that I dare to express and to propose an amendment to the Organic Law of Political Parties in order to eliminate the subsidy provided by the State for these, which bring positive effects in favor of the country. Likewise in the development of the thesis we can see that amount allocated to parties and the use, what rules should be followed to keep shaped and we should do to employ new ways of doing political campaign, involving less expenditure for the same and once the state subsidy, which could make these amounts removed.